An artificial diet containing plant pollen for the mealybug predator Cryptolaemus montrouzieri. Issue 3 (2nd June 2016) - Xie, Jiaqin; Wu, Hongsheng; Pang, Hong; De Clercq, Patrick
Abstract: BACKGROUND: The specialist predatory ladybird Cryptolaemus montrouzieri is an effective natural enemy of mealybugs and plays a key role in the biological control of these pests. However, its mass production is complicated by the dependence on parallel cultures of mealybugs or the need for Ephestia kuehniella eggs as an expensive factitious prey. RESULTS: Here we developed a pollen‐based artificial food for the predator to lower its dependence on natural prey. We found that this artificial diet was an effective alternative food for larvae and adults of this predator. The artificial food supported the development and reproduction of the predator not only in the first generation (F0) but also in the next generation (F1). Although the developmental time and preoviposition period of C. montrouzieri on the artificial food were ca 1.5 days and 4 days longer than on the natural prey, the citrus mealybug Planococcus citri, respectively, its immature survival, fecundity and egg hatch were similar to those on mealybugs. In addition, adult C. montrouzieri maintained on natural or artificial food had a similar starvation resistance. CONCLUSIONS: Our results suggest that the pollen‐based artificial diet can be used as an alternative food in the rearing of C. montrouzieri, and indicate its potential to support the mass production and wider application of this predator in biological control programmes. © 2016 Society of Chemical Industry